Pengaruh Sikap, Norma Subjektif, dan Kontrol Keperilakuan yang Dirasakan Terhadap Niat Mahasiswa Akuntansi Untuk Menjadi Wirausaha Studi Pada Universitas Ahmad Dahlan Yogyakarta - Indriyadi Indriyadi; Sumaryanto Sumaryanto (Universitas Ahmad Dahlan, 2012)
The research to know influence of attitude, subjective norm, and perceived behavioral control to intention accountancy student become entreprenur. The population is accountancy student at Ahmad Dahlan University. Researcher to use purposive sampling with 40 responden. The result of the research that attitude and subjective norm did't significan influence to accountancy student become entrepreneur. Felt behavior supervision influence to accountancy student at Ahmad Dahlan University become entrepreneur.